From Election to Coup The 2006 Campaign and its Aftermath - Fraenkel, Jon (ANU Press, 2007)
In May 2006 Fiji held its tenth general election since independence in 1970. In a country with an unenviable history of electoral trauma, the mood was apprehensive if not tense - not least because of controversial public statements against the incumbent Qarase government being made by the commander of Fiji's military forces. Despite a record number of parties and candidates, the winners were the two big parties - the heavily church-backed SDL, the party of choice of the majority of indigenous Fijians; and the Fiji Labour Party, the party preferred by most Indo-Fijians. Although the result was ethnically polarised, for the first time in Fijian history the successful candidates came together to share power in a constitutionally ordained multiparty cabinet, with Laisenia Qarase retaining the prime ministership. But the fragile collaboration was short-lived. On 5 December 2006, Commodore Voreqe Bainimarama ordered a military takeover, declaring himself 'President', ousting the elected government and replacing it with an 'interim' government of his choice, and once again throwing Fiji into political turmoil. With contributions from ex-Vice President Ratu Joni Madraiwiwi, ousted Prime Minister Laesenia Qarase, leader of the Fiji Labour Party and now interim Minister for Finance Mahendra Chaudhry, and an impressive array of leading commentators on Fijian affairs, this book provides a comprehensive and penetrating analysis of the lead-up to, the outcome and the aftermath of Fiji's historic 2006 election. Shedding light on the complex weave of traditional chiefly systems, race relations, economics, constitutionality, the military ethos and religion, From Election to Coup in Fiji is essential reading for anyone with an interest in Fiji, the South Pacific and the politics of divided societies.